2013
DOI: 10.1371/journal.pone.0076422
|View full text |Cite
|
Sign up to set email alerts
|

Somatic Donor Cell Type Correlates with Embryonic, but Not Extra-Embryonic, Gene Expression in Postimplantation Cloned Embryos

Abstract: The great majority of embryos generated by somatic cell nuclear transfer (SCNT) display defined abnormal phenotypes after implantation, such as an increased likelihood of death and abnormal placentation. To gain better insight into the underlying mechanisms, we analyzed genome-wide gene expression profiles of day 6.5 postimplantation mouse embryos cloned from three different cell types (cumulus cells, neonatal Sertoli cells and fibroblasts). The embryos retrieved from the uteri were separated into embryonic (e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
2

Relationship

4
5

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 48 publications
0
13
0
Order By: Relevance
“…Furthermore, extraembryonic tissues of SCNT-derived conceptuses also showed an abnormal phenotype shortly after implantation. They had a proliferative deficiency caused by precocious differentiation, leading to poor development of the ectoplacental cone and cytotrophoblast areas at implantation sites [7,8]. Based on these cumulative findings, we speculate that some unidentified epigenetic errors are inherent to extraembryonic lineages derived by SCNT throughout development.…”
Section: Introductionmentioning
confidence: 79%
See 1 more Smart Citation
“…Furthermore, extraembryonic tissues of SCNT-derived conceptuses also showed an abnormal phenotype shortly after implantation. They had a proliferative deficiency caused by precocious differentiation, leading to poor development of the ectoplacental cone and cytotrophoblast areas at implantation sites [7,8]. Based on these cumulative findings, we speculate that some unidentified epigenetic errors are inherent to extraembryonic lineages derived by SCNT throughout development.…”
Section: Introductionmentioning
confidence: 79%
“…The IG-DMR regulates many imprinted genes within its region for their parental originspecific expressions in the developing fetus and placenta. Indeed, upregulation of Dlk1, one of the IG-DMR-regulated genes, is often associated with death in early cloned fetuses, probably because of hypermethylation of the IG-DMR [7,9]. It is probable that the abnormal development of placentas in cloned mice is also affected by the hypermethylated IG-DMR.…”
Section: Resultsmentioning
confidence: 99%
“…Thus, somatic-type LOCKs might affect the epigenetic status and gene expression patterns of SCNT-derived embryos, and prevent proper genome reprogramming and term development. Indeed, microarray analysis of single SCNT-derived embryos revealed that they had a unique gene expression profile that was strictly dependent upon the type of donor cells [34,38,42]. In other words, it is expected that SCNT-derived embryos from differentiated somatic cells with low levels of H3K9me2 might have few LOCKs and enhance the efficiency of mouse cloning.…”
Section: Introductionmentioning
confidence: 99%
“…Intriguingly, SCNT embryos also showed Xist-independent correction of gene expression profiles, indicating the presence of extensive reprogramming of the genomic state during implantation. 23 This NT study has demonstrated that, in mouse embryos, the maternal Xist-repressing imprint is also erased in placental tissues, specifically before day 4.5. Therefore, in a strict sense, the preferential inactivation of the paternal X chromosome in the mouse placentas is not imprinted but may be "biased" or "skewed" (Fig.…”
Section: Discussionmentioning
confidence: 89%